High throughput immuno-screening of cDNA expression libraries produced by in vitro recombination; exploring the Plasmodium falciparum proteome - Kordai Sowa, M.P.; Sharling, L.; Humphreys, G.; Cavanagh, D.R.; Gregory, W.F.; Fenn, K.; Creasey, A.M.; Creasey, A.M.
Improved Plasmodium falciparum cDNA expression libraries were constructed by combining mRNA oligo-capping with in vitro recombination and directional cloning of cDNA inserts into a plasmid vector that expresses sequences as thioredoxin fusion proteins. A novel procedure has also been developed for the rapid identification of seropositive clones on high-density filters, using direct labelling of P. falciparum immune immunoglobulin with fluorescein isothiocynate (FITC). This approach combines the advantages of recombination-assisted cDNA cloning with high throughput, non-radioactive serological screening of expression libraries. Production of replicate colony matrices allows the identification of antigens recognised by different pools with different specificities from residents of a malaria endemic region. Analyses ofDNAsequences derived from sero-reactive colonies indicate that this is an effective method for producing recombinant proteins that react with antibodies from malaria-exposed individuals. This approach permits the systematic construction of a database of antigenic proteins recognised by sera from malaria-exposed individuals.
Keywords: PLASMODIUM FALCIPARUM; CDNA; IN VITRO RECOMBINATION; PROTEIN MACRO-ARRAY